THE BENEFITS OF FERMENTED GOAT’S MILK WHEY MASK WITH HONEY AND RED FRUIT (Pandanus conoideus) AS ANTIOXIDANT AGENT - Pratiwi, Yulia Yasmin; Arief, Irma Isnafia; Soenarno, M.Sriduresta (Malaysian Journal of Science, 2023)
Goat’s milk fermented whey, honey, and red fruit extract can be used for making face masks because they can increase the effectiveness of mask. Whey has smaller fat globules so it helped nutrients absorbed better in to the skin, the honey and red fruit contain flavonoids and phenolics to keep skin moist, clean, and it also produced the antioxidant properties of fermented whey masks. This study aimed to determine the formulation of the fermented whey mask as well as its physical characteristics and antioxidant properties. Fermented whey masks were tested for their physical characteristic such as pH, water activity, spreading ability, drying time and antioxidant properties to see which formulation produced a mask with good test results. The study was tested using a completely randomized factorial design. Result showed that mask with addition of 10% honey had better physical characteristic such as pH, water activity, spreading ability, drying time and antioxidant activity than the addition of 5% honey. Results gained from this study were prospected to be developed into the shelf life stability and dermatologically because it has the potential to be developed commercially.